The Gaza Phoenix Recovery Framework: An overview - Salem, Yara; Kittana, Abdalrahman; Gola, Alessandra (Plurimondi, 2025)
Developed amid the destruction of Gaza’s built environment and of life, social networks, and cultural and institutional fabric, this paper introduces the Gaza Phoenix Recovery Framework as a locally led model for recovery. The framework challenges donor-driven reconstruction paradigms that have been shown to marginalise affected communities, as well as approaches that focus exclusively on the post-war period while neglecting recovery during the crisis itself. Grounded in local knowledge, engagement with local administrations, and networked interdisciplinary expertise, the framework pursues recovery by addressing simultaneously the material, social, heritage, and institutional spheres, understood as essential and intertwined components of a dignified, resilient, and just future.